# How do you solve the system #1/3 x - 1/12 y = -7# and #1/3 x + 1/6 y = 11#?

##### 2 Answers

#### Answer:

**x = -3 and y = 72**

#### Explanation:

So we are given with

equation 1 is

equation 2 is

equation 1 can be written as

(multiplied the whole equation by 12)

equation 2 can be written as

(multiplied whole equation by 6)

now we add both the equations

==>

==>

==>

==>

now we substitute

we will get

#### Answer:

#### Explanation:

Both equations have the same

Rewrite both equations:

Substitute to find